SECURITY IMPROVEMENT AND TRUST ENHANCEMENT IN CLOUD-BASED SERVICES - Negi, Shalabh; R, Jayanthi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Management of trust is one of the most challenging parts in cloud computing. Cloud service's features such as distributed, dynamic and nontransparent introduces several challenges for availability, privacy, and security. A method is proposed to have trust as a service between cloud service provider and customer by creating a cloud armor. This proposed methodology is used to make cloud server end and customer end system secure of any intrusion to their privacy. In this methodology, we will have a user usage pattern log as ever user has its own unique way of using his/her system; hence, in case if any odd user pattern is being encountered it will automatically block the system and simultaneously shoots a message as well as a call to the user notifying him/her about this unauthorized access. This log is set a various small pattern log, for example, keylog, preferable website visited, and time of accessing the system. Further, we have secured these logs using Rivest-Shamir-Adleman algorithm with very large key size.